The use of Educational Technologies in public schools during the Covid-19 pandemic (Research, Society and Development, 2021)
The health crisis caused by the Covid-19 pandemic completely changed the education scenario in the country, presenting us a new and challenging situation, imposing on education professionals a routine of distancing that completely broke the link between students and teachers. In view of this fact, it was necessary to implement new pedagogical practices aimed at remote teaching and the insertion of educational technologies that have become indispensable instruments for the teaching and learning process. The objective of this work was to review the literature in search of articles that observed how teachers and students have dealt with the difficulties and obstacles arising from the need to implement remote learning during the pandemic period. As a methodological procedure, a bibliographic research based on a survey of scientific articles made available by researchers in the field of education on the Internet was adopted. Thus, it was evident that understanding the needs of students and teachers, enabling everyone to have access to educational technologies, and helping the school community in its limitations when using the technologies available in the educational network, is essential to reduce the damage to education resulting from the Pandemic.